ANALISIS SEMIOTIKA IKLAN TELEVISI PRODUK ALAT PERTANIAN TRAKTOR âQUICKâ - , ADHITYA TRI DIWA; , Ir. Roso Witjaksono, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The research was conducted to find out the signifier, signified, signification and the messages contained in television commercials visualization of agricultural equipment products tractor âQuickâ. The basic method of this research was descriptive analytical with semiotic analysis technique based on the theory of Ferdinand de Saussureâs sign. This research used supporting data of informants consist of: Chief Marketing CV. Karya Hidup Sentosa and Creative Director of PT. Cipta Citra Senindo. Data were analyzed qualitatively through stages: division of the scene, identification signifier in every scene, purposing the signified and signification of the signifier that identified based on the interpretation of the author and interview. The results showed that television commercials agricultural equipment products tractor âQuickâ using some of signifier to present the signified and signification to be conveyed by the advertiser such as the signifier acrobatic movements with the signified agility and ease of movement and with signification that the tractor is easy to use. Containing messages in television commercials agricultural equipment products tractor âQuickâ is an advertiser wants to cultivate an umbrella brand to the audience that the brand of Kubota tractor, Dongping, G600 tractor, G1000 tractor, G1000 Boxer tractor is Quick.